Distortion and mechanical properties of welded AA5083 aluminum material with friction stir welding - Pujono, Pujono; Kurniawan, Ipung; Pribadi, Joko Setia; Laksana, Nur Akhlis Sarihidaya; Tarigan, Roy Aries Permana (Jurnal Polimesin, 2025)
AA5083 series aluminum is one of the primary materials used in ship construction due to its excellent weldability in conventional welding processes, such as arc welding. However, similar to other aluminum alloys, the weakness of AA5083 is the occurrence of frost cracking during the welding process, especially in the HAZ and the large amount of distortion.. The research was conducted by providing additional treatment in the form of in-situ rolling on friction stir welding (FSW). The in-situ rolling treatment used a single roll positioned directly on the weld area and behind the FSW tool and moving simultaneously with the welding process and with a roll load of 8000N. The characterization carried out included thermal cycle measurements, microstructure observations, hardness value distribution testing, distortion measurements and tensile testing. The results showed that the largest distortion value occurred in the welded material without additional treatment (as welded) of 2.81 mm, while in the material with additional treatment (mechanical), the distortion value was smaller at 1.1 mm. The mechanical specimen had the best mechanical qualities, with a tensile strength of 225.5 MPa and an average hardness value of 61 VHN, whereas the as-welded specimen's tensile strength was 201.8 MPa. This phenomenon occurs because the specimen, with the addition of in situ rolling, experiences grain refinement, and it seems that this is consistent with the Hall-Petch relationship, σ_y=σ_0+k_y d^(-1/2)Materials with fine grains are harder and stronger than materials with coarse grains, because fine grains have a larger total grain boundary area to hinder dislocation movement. The tensile fracture position was in the advancing side region, where higher heat input occurred in this region than in the retreating side.